Cost Estimation Process for Automotive Component - Razvan Adrian GUDANA; Irina SEVERIN; Florina Daniela LASCU (Communications of International Proceedings, 2021)
The activity of cost estimation plays an important role in making strategic and operational decisions in an organization. Over time, it has been shown that an organization which can estimate its costs more accurately than its competitors, enjoying a competitive advantage in the market place. This case study has been started from the necessity of cost estimation department within a Romanian car manufacturer, to improve the standard time allocated to a request in the cost estimation process. The data inputs have been collected from the department and results were compared using different quality tools. The main purpose of this paper is to identify and quantify a tool which will help to reduce the allocated time for material change estimation using DMAIC (Define, Measure, Analyze, Improve, Control) concept which is considered as an elaboration of improvement methods, the addition of concepts, methods, tools. It draws on the knowledge of the field of quality engineering, integrating ideas of total quality, management and quality control beyond control limits. By improving the cost estimation process, will then bring value added within setting the target, sourcing and price negotiation processes. Therefore, a practical solution has been brought into the cost estimation process so the material change estimation request allocated time was reduced up to 0.75 hours.
Keywords: Component; Cost Estimation; DMAIC; Target Setting; Process Improvement.